TINGKAT PERBEDAAN KEMAMPUAN BTAQ METODE IQRO’ DAN UMMI PADA SISWA SD MUHAMMADIYAH WIROBRAJAN II YOGYAKARTA - Sri Agustinawati; Adhy Pratomo Yunianto Herlambang; Nawari Nawari; Aris Fauzan (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
The objectives of this study are : (1) to analyze the real condition of students’achievements in SD Muhammadiyah Wirobrajan II in implementing Iqro method,(2) To analyze the real condition of students’ achievements in SD Muhammadiyah Wirobrajan II in implementing Ummi Method, (3) to examine whether thereis asignificant difference or not between the students’ ability after they implement Iqro’ and Ummi Method at SD Muhammadiyah Wirobrajan II, and (4) to measure whichmethod is better between Iqro and Ummi Method to enhance the students’ abilityto read al-Quran. This study constitutes a comparative and descriptive quantitative research.The subjects of this studyare students at SD Muhammadiyah Wirobrajan II Yogyakarta. The data gathering methods use practice scores, documentation, interview and questionnaires. The data analysis techniques utilize quantitative descriptive statistics and t test analysis. The research findings show that 1) the t-tes analysis indicates that t calculated = 17,687 is bigger than t table = 1,988. (t calculated > t table (5%) =17,687 > 1,988). This means that there is a significant difference between students who implement Iqro and Ummi methods. 2) The average score of students that use Ummi method is 87,61. This score is more than the average score of students that implement Iqro method 82,17. This means that Ummi method is better than Iqromethod to improve the students’ ability to read al-Quran.